(untitled) (Harmoni, 2018)
Being granted of various religions and ethnicity, the people of Pematang Siantar could live harmoniously and free of religious-ethnic conflicts. The source of this paper is gained from a research applying anthropological-qualitative methods. The objective is to understand concept and thought, as well as to look at and observe the spirit of multiculturalism developed by the people of Pematang Siantar in maintaining their harmony. The data collection applies techniques of observation and deep interview, whereas the data is analysed interpretively by applying techniques of triangular analysis together with emic and etic perspectives. The result demonstrates that the harmony within the pluralistic society of Pematang Siantar could be maintained for within the people life, there have been developed collective awareness of plurality. Nevertheless, the society keep developing critical attitudes through the movement of multiculturalism that has been socially reproduced by applying internal perspective, namely the development of tolerant habit, the conservation of kinship system and tradition, the rejection of primordialism, and the application of the politic of multiculturalism.